Ice Tube Maker Maintenance Services Reliable Solutions for Your Equipment: Layanan Perawatan Pembuat Tabung Es Solusi Terpercaya untuk Peralatan Anda - Wicaksono, Arief Tri; Jamaluddin (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the impact of maintenance on the performance and longevity of ice tube maker machines, crucial for cooling in regions like Indonesia with consistently high temperatures. Utilizing a methodical approach, the research focuses on selecting quality raw materials and monitoring ice cube production to determine maintenance intervals. Results highlight the significance of timely maintenance in sustaining machine efficiency and extending service life, ultimately ensuring consistent ice quality. Additionally, the study underscores the correlation between operational stability, electricity source reliability, and component workload. Findings emphasize the necessity of proper maintenance protocols to uphold machine functionality and productivity in challenging environments, offering implications for improved cooling technology worldwide. Highlights : Timely maintenance intervals crucial for machine longevity and efficiency. Quality raw material selection influences ice cube production and overall performance. Stable electricity sources vital for operational consistency and component workload management. Keywords: Ice Tube Maker, Maintenance Practices, Machine Performance, Cooling Technology, Operational Stability